Beneficiation of Copper Slag by Hydrometallurgical Method - N. Acarkan (International Mineral Processing Congress, 2014)
Slags usually contain some quantity of valuable metals. They are actually a secondary resource of metals, rather than an end-waste and have been utilized as a resource material in many areas. In addition, for some applications, slags have comparable or even better properties than their competitors. Leaching is a method for extraction of metals from copper slags. The extraction of metals such as copper and cobalt from the copper slag of Küre-Turkey, was investigated in the past decades. Fayalitic type of these copper slags containing 0.934 % Cu, 0.353 % Co and 50.91% Fe were subjected to the experimental study. As a result of mineralogical analysis of the slag sample, fayalitic type of slag was found to contain hercynite, magnetite, hematite, pyrite, chalcopyrite, covellite, bornite and metallic copper. Direct acid leaching methods were applied on the sample. Effects of leaching time, temperature and acid concentration on Cu and Co leaching recoveries were investigated in the direct acid leaching. The optimum leaching conditions were found as leaching time of 2 hours, solid/liquid ratio of 1/3, H2SO4 concentration of 125 g/L and temperature of 70 °C. At these conditions, 75.5 % of Cu, 95.6 % of Co and 70.9 % Fe were extracted. In the second stage of the leaching experiments, copper in the pregnant solution was precipitated by cementation to produce a Cu concentrate assaying 95.58 % Cu; cobalt was obtained by precipitation with H2S to produce a concentrate containing 62.10 % Co. As a result of this study a process flow sheet has been developed for recovering Cu and Co from these slags to demonstrate its economic and technological benefits.